Composite powders from low energy density explosive. Issue 172 (12th June 2016) - Sheng, Zhou Hui; Hua, Xie Xing; Kang, Xu
ABSTRACT: Nanostructured spinel lithium manganese oxide (LiMnO) was synthesized for the first time by explosive method. The water-solubility explosive was prepared using a simple facility at room temperature. The growth of lithium manganate via combustion reaction was investigated with respect to the presence of an energetic precursor, such as the metallic nitrate and the degree of confinement of the explosive charge. The combustion products were characterized by scanning electron microscopy. Powder X-ray diffraction and transmission electron microscopy were used to characterize the products. Lithium manganate with spherical morphology and more uniform secondary particles, with smaller primary particles of diameters from 10 to 30 nm and a variety of morphologies were found. Lithium manganate with a fine spherical morphology different from that of the normal spinel is formed after combustion wave treatment due to the very high quenching rate. It might also provide a cheap large-scale synthesis method. Explosive combustion is strongly nonequilibrium processes, generating a short duration of high pressure and high temperature. Free metal atoms are first released with the decomposition of explosives, and then theses metal and oxygen atoms are rearranged, coagulated and finally crystallized into lithium manganate during the expansion of combustion process.